Caracterización de los parámetros físicos y químicos de los efluentes de agua al río Cutuchi en el sector Lasso cantón Latacunga provincia Cotopaxi, periodo 2015 - Yánez Quinatoa, Elizabeth Gabriela (2015)
Water is the most abundant substance on earth and is the ideal and essential for life environment. The quality of this resource depends on natural factors and human action; use in various industrial activities alters the physical chemical characteristics of the water seriously affecting the existence of ecosystems. There has been no natural or anthropic recuperation of the river since the industrial growth of the lasso sector, far from having fount a solution, the estate of Cutuchi River has worsened due to the leakage from the industry that has continued to increase, converting the river in to a receptor of residual water. This is one of the principal problems affecting the river, making it a center of contamination….